Ownership structure, board characteristics and dividend policy: evidence from the Warsaw Stock Exchange - Pieloch-Babiarz, Aleksandra (Ekonomia i Prawo. Economics and Law, 2019)
Motivation: The ownership structure is a frequently undertaken research issue on the dividend determinants. However, there are not many scientific studies conducted on the Warsaw Stock Exchange (WSE) which investigate the ownership structure of dividend payers in the context of board characteristics (i.e. board composition, board independence or chairman entrenchment). Therefore, a research gap has been observed in this area and an appropriate study has been conducted. Aim: The aim of the paper is to investigate the links between the ownership structure of publicly traded companies and the dividend pay-outs in the context of board characteristics. Results: Empirical research has been conducted on a group of 354 non-financial companies listed on the WSE. The results of the study indicate that in the companies that pay out dividend one can observe a greater share of both the institutional investors and the State Treasury. The board of such companies is bigger, the board members more often hold shares and the chairman occupies the position for a longer time. Moreover, the propensity to pay dividend and dividend amount increase if there is an increase in institutional ownership, board duality and chairman entrenchment.